2016
DOI: 10.3389/fnhum.2016.00477
|View full text |Cite
|
Sign up to set email alerts
|

Depression-Related Brain Connectivity Analyzed by EEG Event-Related Phase Synchrony Measure

Abstract: This study is to examine changes of functional connectivity in patients with depressive disorder using synchronous brain activity. Event-related potentials (ERPs) were acquired during a visual oddball task in 14 patients with depressive disorder and 19 healthy controls. Electroencephalogram (EEG) recordings were analyzed using event-related phase coherence (ERPCOH) to obtain the functional network. Alteration of the phase synchronization index (PSI) of the functional network was investigated. Patients with dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 37 publications
6
16
0
Order By: Relevance
“…That is similar to our results, in which intrahemispheric coherence was lower for delta band in depressive patients. Also, Li et al [18] stated that decrease in delta in major depression indicated impairment of the connection between the frontal and parietal/ temporal/occipital regions. He explained that the increase in theta, alpha and beta in the frontal/ prefrontal sites might reflect the compensatory mechanism to maintain normal cognitive performance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…That is similar to our results, in which intrahemispheric coherence was lower for delta band in depressive patients. Also, Li et al [18] stated that decrease in delta in major depression indicated impairment of the connection between the frontal and parietal/ temporal/occipital regions. He explained that the increase in theta, alpha and beta in the frontal/ prefrontal sites might reflect the compensatory mechanism to maintain normal cognitive performance.…”
Section: Discussionmentioning
confidence: 99%
“…EEG coherence studies in patients with depression showed different results. Some studies for patients with depressive disorder reported reduced coherence values compared to healthy controls [15][16]; other studies showed significantly higher overall or partial coherence in patients with major depressive disorder as compared to controls [17][18][19]. Opposite to those studies, Suhhova et al [20] demonstrated no sig-INTER-AND INTRA-HEMISPHERIC EEG COHERENCE STUDY IN ADULTS WITH NEUROPSYCHIATRIC DISORDERS nificant changes in the EEG coherence between healthy subjects and patients with depression.…”
Section: Introductionmentioning
confidence: 99%
“…In the resting-state condition, major depression is characterized by unique EEG oscillations in beta frequencies that are dominant in relation to delta, theta, and alpha oscillations 7 , and this oscillatory pattern was never seen in healthy subjects. Another study has reported increased theta and beta phase synchronization in major depression related to attentional deficit in the visual oddball task 12 . In the present study, we hypothesized that disorganization of oscillation synchronization with abnormal theta and beta oscillation synchronization would be identifiable in a neuronal network involved in working memory processing in major depression, and that this would provide new insights into the unstable state of cognitive processing and advance our understanding of functional aspect of beta oscillations in the brain.…”
Section: Introductionmentioning
confidence: 98%
“…They may seem focused externally, but their mental focus may be influenced by the sad aspects of the video. However, another study by Li et al found that higher Beta activities were found in connection with electrodes at the dorsolateral prefrontal cortical or temporal regions [23].…”
Section: Results and Discussion 31 Phq-9 Screening Score And Eeg Measurementioning
confidence: 95%
“…The low Alpha EEG amplitude at these electrode channels may be due to that these subject are less sensitive to be in contact with the surround environment as they are more focused with their inner selves [14]. Research by Li et al discovered opposite findings where those with major depressive disorder showed widespread and significant increases in Alpha and Theta band [23]. The mean EEG amplitudes of Beta () for the four (4) different depressed groups are presented in Figure 5.…”
Section: Results and Discussion 31 Phq-9 Screening Score And Eeg Measurementioning
confidence: 98%